2016
DOI: 10.1590/1517-869220162203136466
|View full text |Cite
|
Sign up to set email alerts
|

Kinesio Taping Não Altera a Relação Emg Entre Vasto Lateral E Vasto Medial Durante Meio-Agachamento

Abstract: RESUMOIntrodução: Kinesio Taping é uma técnica realizada com aplicação de fitas elásticas sobre a pele, que se propõe a produzir determinados efeitos com fins de prevenção e tratamento das lesões musculoesqueléticas. No entanto, os meios pelos quais tais efeitos ocorrem continuam sendo investigados e discutidos, principalmente no que diz respeito à utilização no campo da reabilitação e do esporte. Objetivo: Analisar a relação da atividade eletromiográfica encontrada nos músculos vasto lateral (VL) e vasto medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…They suggest that the main effect of KT is to facilitate muscle spindle reflex through the retraction effect by means of dynamic actions, activating the mechanoreceptors necessary to facilitate muscle contraction and that this may not be achieved in isometric exercise. However, as already discussed, there is evidence that points to the absence of alteration in muscle activation during dynamic exercises [22,35] and in different percentages of tape stretching [23] and which support the findings of this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They suggest that the main effect of KT is to facilitate muscle spindle reflex through the retraction effect by means of dynamic actions, activating the mechanoreceptors necessary to facilitate muscle contraction and that this may not be achieved in isometric exercise. However, as already discussed, there is evidence that points to the absence of alteration in muscle activation during dynamic exercises [22,35] and in different percentages of tape stretching [23] and which support the findings of this study.…”
Section: Discussionsupporting
confidence: 92%
“…This fact corroborates other findings in the literature, such as Cai et al [34], who were unable to verify significant changes in the neuromuscular activity of the wrist extensor muscles and maximum grip strength immediately after the application of different use conditions of KT (facilitative and inhibitory). Such behavior seems to be independent of the size or type of muscle grouping, since Serrão et al [35] also found no increase in myoelectric activity of the vastus lateralis and vastus medialis muscles when performing half-squat exercise after KT application in trained individuals. Similar results was reported by Dos Santos Glória [22], who tested the isometric and dynamic strength of professional soccer players and found no change in rectus femoris muscle activation after KT application.…”
Section: Discussionmentioning
confidence: 94%